Switching to olanzapine long-acting injection from either oral olanzapine or any other antipsychotic: comparative post hoc analyses - Ciudad A (Dove Medical Press, 2013)
Antonio Ciudad,1 Ernie Anand,2 Lovisa Berggren,3 Marta Casillas,4 Alexander Schacht,3 Elena Perrin5 1Department of Clinical Research and Development, Eli Lilly & Co, Madrid, Spain; 2Neuroscience Medical Affairs – EU, Lilly Research Centre, Windlesham, Surrey, UK; 3Global Statistical Sciences, Eli Lilly & Co, Bad Homburg, Germany; 4European Scientific Communications, Eli Lilly & Co, Madrid, Spain; 5Medical Department, Eli Lilly & Co, Suresnes, Paris, France Background: A considerable proportion of patients suffering from schizophrenia show suboptimal responses to oral antipsychotics due to inadequate adherence. Hence, they are likely to benefit from switching to a long-acting injectable formulation. These post hoc analyses assessed the clinical effects of switching to olanzapine long-acting injection (OLAI) from either oral olanzapine (OLZ) or other antipsychotics (non-OLZ). Methods: Post hoc analyses were done based on two randomized studies (one short-term, one long-term) conducted in patients suffering from schizophrenia and treated with OLAI. The short-term study was an 8-week placebo-controlled, double-blind trial in acute patients, and the long-term study was a 2-year, oral olanzapine-controlled, open-label, follow-up of stabilized outpatients. Results: These analyses used data from 62 OLAI-treated patients (12 switched from OLZ, 50 from non-OLZ) from the short-term study and 190 OLAI-treated patients (56 switched from OLZ, 134 from non-OLZ) from the long-term study. Kaplan–Meier survival analyses of time to all-cause discontinuation of OLAI treatment did not differ significantly between OLZ and non-OLZ patients in the short-term study (P=0.209) or long-term study (P=0.448). Similarly, the proportions of OLZ and non-OLZ patients that discontinued OLAI were not statistically different in the short-term (16.7% versus 36.0%, respectively; P=0.198) or long-term (57.1% versus 47.8% respectively; P=0.238) studies. In the short-term study, no significant differences were detected between the patient groups in mean change in Positive and Negative Syndrome Scale (PANSS) total score (-13.4 OLZ versus -20.8 non-OLZ; P=0.166). In the long-term study, mean change in PANSS total score (3.9 OLZ versus -3.6 non-OLZ; P=0.008) was significantly different between the non-OLZ and OLZ groups. Rates of treatment-emergent adverse events were similar in OLZ and non-OLZ groups per study. Conclusion: These post hoc analyses suggest that no significant differences in clinical effectiveness were seen after switching from non-OLZ or OLZ to OLAI. However, these findings should be interpreted with care, due to small sample sizes and differences in patients' clinical profiles. Keywords: schizophrenia, olanzapine, long-acting injection, depot formulation